1996
DOI: 10.1093/jnci/88.14.956
|View full text |Cite
|
Sign up to set email alerts
|

UCN-01: a Potent Abrogator of G2 Checkpoint Function in Cancer Cells With Disrupted p53

Abstract: UCN-01 is a potent abrogator of G2 checkpoint control in cancer cells with disrupted p53 function. UCN-01 might be capable of enhancing the effectiveness of DNA-damaging agents in the treatment of tumors with cells lacking normal p53 function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
291
2
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(319 citation statements)
references
References 28 publications
23
291
2
3
Order By: Relevance
“…It has been reported to sensitize various cancer cells to variant DNA-damaging agents such as cisplatin (Wang et al, 1996), topoisomerase I inhibitors (Shao et al, 1997) or gemcitabine (Shi et al, 2001). However, the usage of UCN-01 on Chk1 inhibition was not totally successful since its untoward toxicities and non-specific inhibition decrease the value as a Chk1 inhibitor (Sausville et al, 2001).…”
Section: Figure16 Schematic Representation Of the Effect Of Chk1 Onmentioning
confidence: 99%
“…It has been reported to sensitize various cancer cells to variant DNA-damaging agents such as cisplatin (Wang et al, 1996), topoisomerase I inhibitors (Shao et al, 1997) or gemcitabine (Shi et al, 2001). However, the usage of UCN-01 on Chk1 inhibition was not totally successful since its untoward toxicities and non-specific inhibition decrease the value as a Chk1 inhibitor (Sausville et al, 2001).…”
Section: Figure16 Schematic Representation Of the Effect Of Chk1 Onmentioning
confidence: 99%
“…Although treatment with 25 nM UCN-01 (a non-toxic dose in S/RG/C2) abrogated the IR-induced G2 checkpoint in S/ RG/C2 (Table 1), there was no evidence of radiosensitisation in this cell line (Figure 2). It was of interest, therefore, to determine whether a higher dose of UCN-01 (300 nM) for a shorter treatment period (24 h) (a protocol described previously (Wang et al, 1996)), would be more effective at abrogation of the G2 checkpoint and would result in sensitisation to IR-induced cell death in the S/RG/ C2 cell line which was not previously sensitised. In both the HT29 and S/RG/C2 cell lines, treatment with 300 nM UCN-01 effectively abrogated the IR-induced G2 arrest.…”
Section: A Higher Dose Of Ucn-01 Does Not Radiosensitise S/rg/c2mentioning
confidence: 99%
“…Previous work by Wang et al (1996) has shown that UCN-01 sensitises the colorectal carcinoma cell line HT29 to IR-induced growth inhibition, however, it is not known whether this is a general response of all colorectal tumour cells. Given the frequent use of radiotherapy in treatment of colorectal cancer and the potential importance of this therapeutic strategy, the aim of this study was to determine whether UCN-01 was able to abrogate the IR-induced G2 arrest in a range of colorectal tumour cell lines, and whether this would consistently lead to radiosensitisation in these cell lines.…”
mentioning
confidence: 97%
See 2 more Smart Citations